Hypertension, inflammation and T lymphocytes are increased in a rat model of HELLP syndrome. (February 2014) - Wallace, Kedra; Morris, Rachael; Kyle, Patrick B.; Cornelius, Denise; Darby, Marie; Scott, Jeremy; Moseley, Janae; Chatman, Krystal; LaMarca, Babbette
<x xml:space="preserve">Abstract</x> Objective: An animal model of hemolysis, elevated liver enzymes, low platelet count (HELLP) was used to determine if T lymphocytes accompany hypertension and increased inflammatory cytokines. Methods: sFlt-1 (4.7 µg/kg/day) and sEndoglin (7 µg/kg/day) were infused into normal pregnant rats (HELLP rats) for 8 days. Results: HELLP was associated with increased mean arterial pressure (p = 0.0001), hemolysis (p = 0.044), elevated liver enzymes (p = 0.027), and reduced platelets (p = 0.035). HELLP rats had increased plasma levels of TNFα (p = 0.039), IL-6 (p = 0.038) and IL-17 (p = 0.04). CD4+ and CD8+ T lymphocytes were increased. Conclusion: These data support the hypothesis that T cells are associated with hypertension and inflammation.